Social and cultural capital in multicultural campuses: Effects on tolerance among multiethnic students - Mustafida, Fita; Sulistiani, Ika Ratih; Mohammad Hakim, Dian; Aliffiati; Fatinatul Fitroh , Sayyidah (Journal of Interdisciplinary Studies in Education, 2026)
This study examines how social and cultural capital influences students’ tolerance in multicultural university settings. A survey of 191 Ma Chung University and Udayana University students in Indonesia revealed that both social capital (networks, trust, and participation) and cultural capital (knowledge, experience, and exposure) significantly predict attitudes toward tolerance (β = 0.35 and β = 0.39, p < 0.05), explaining 43% of the variance (R² = 0.43). Students involved in multicultural activities and strong social networks showed greater acceptance of diversity. These findings underscore the importance of institutional strategies to promote inclusive campus environments by developing students’ social and cultural capital. Future research should investigate the long-term effects and accessibility challenges faced by minority groups in multicultural programs.